q+6=-9

Simple and best practice solution for q+6=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for q+6=-9 equation:


q+6=-9

We simplify the equation to the form, which is simple to understand
q+6=-9

We move all terms containing q to the left and all other terms to the right.
+1q=-9-6

We simplify left and right side of the equation.
+1q=-15

We divide both sides of the equation by 1 to get q.
q=-15

See similar equations:

| 7x=9x+20 | | 3a-4=5-2a | | (8x^3+4x^2)-(5x^2-12x)= | | 10=8(7y-6)-27y+30 | | 4(x+1)=8-3(4x+4) | | -4(4x-8)=-16 | | -4(1-7k)=164 | | 14+5c=4c | | 27-3x=-3(-1+5x) | | 3x+4=8-0.5 | | e-7=-6 | | -g+2(3+g)=-4g+1 | | -6(5-x)+3=3(x-1) | | j+2=-1 | | 7x-6=-13 | | -2u-18=0 | | 5-1-2x=12 | | 700x-35=450x+15 | | Z-38=-46 | | 3(5-x^2)-5= | | 2+k=-9 | | 1.8C+32=32.9 | | 11x-15y=23 | | -5-12+13p=11p-3 | | 8+3x=.5(16+16x) | | 10-6v=-94 | | 4j-5=150 | | -3k=31 | | 6=-7x+27 | | -6+12r=14r-20 | | 5(4+2x)=9(x-5) | | x-8.3=-5.3 |

Equations solver categories